This is the grassroots Aboriginal people's address to the nation and reply to Mr Howard and the forewarning to the population of people of Australia - R. Bropho; M. Wanjurri-Nungala; . Yaluritja (Law Text Culture, 1998)
We say this to the Population of people of Australia: what is said here is what is going to happen if you go through with this 10 point Wik Plan and by that you dispossess us the Original Owners of our last bit of land, our last bit of Hope. You must know these things because you can't see what we can see because we have lived through it for 200 years. Let us the grassroots Aboriginal people, the Nation of Aboriginal people say unto you Mr Howard as the Prime Minister, and to Mr Minchin and Mr Fischer and to Senator Harradine and also to Mr KIm Beazley and all the Labor people and the Greens and the Democrats ...